Synergistic antibacterial efficacy of early combination treatment with tobramycin and quorum-sensing inhibitors against Pseudomonas aeruginosa in an intraperitoneal foreign-body infection mouse model - Jakobsen, Tim H. (2013)
Objectives:Quorum sensing (QS)-deficient Pseudomonas aeruginosa biofilms formed in vitro are more susceptible to tobramycin than QS-proficient P. aeruginosa biofilms, and combination treatment with a QS inhibitor (QSI) and tobramycin shows synergistic effects on the killing of in vitro biofilms. We extended these results to an in vivo P. aeruginosa foreign-body biofilm model. The effect of treatment initiated prophylactically was compared with treatment initiated 11 days post-insertion. Methods:Silicone tube implants pre-colonized with wild-type P. aeruginosa were inserted into the peritoneal cavity of BALB/c mice. Mice were treated with intraperitoneal or subcutaneous injections of the QSIs furanone C-30, ajoene or horseradish juice extract in combination with tobramycin. Mice were euthanized on day 1, 2, 3 or 14 post-infection for the estimation of quantitative bacteriology, histopathology and cytokine measurements. Results:Combination treatment of P. aeruginosa resulted in a significantly lower cfu per implant as compared with the placebo groups for all QSIs tested. For early-initiated treatment, a significant difference in clearing was also observed between the combination group and the single-treatment groups, and between the placebo group and the single-treatment groups. In one case a significant difference in clearing was found between the two single-treatment groups. Conclusions:Synergistic antimicrobial efficacy could be achieved when treating mice with both a QSI and tobramycin, resulting in an increased clearance of P. aeruginosa in a foreign-body infection model. Our study highlights the important prospects in developing an early combinatory treatment strategy for chronic infections.